Targeted Genome Reduction of Pseudomonas aeruginosa Strain PAO1 Led to the Development of Hypovirulent and Hypersusceptible rDNA Hosts - Grosjean, Mélanie; Guénard, Sophie; Giraud, Caroline; Muller, Cédric; Plésiat, Patrick; Juarez, Paulo (Frontiers in Bioengineering and Biotechnology, 2021)
Pseudomonas aeruginosa is a human opportunistic pathogen responsible for nosocomial infections which is largely used as a model organism to study antibiotic resistance and pathogenesis. As other species of the genus, its wide metabolic versatility appears to be attractive to study biotechnological applications of this bacterium. However, its natural resistance to antibiotics and its capacity to produce a wide range of virulence factors have failed to evaluate the biotechnological potential of this species. By reducing the genome of the reference strain PAO1, we explored the development of four hypovirulent and hypersusceptible recombinant DNA hosts (rDNA hosts). Despite deleting up to 0.8% of the core genome, any of the developed strains presented alterations of fitness when cultured under standard laboratory conditions. Other features such as antibiotic susceptibility, cytotoxicity, in vivo pathogenesis, and expression of heterologous peptides were also explored to highlight the potential applications of these models. This work stands as the first stage of the development of a safe-platform strain of Pseudomonas aeruginosa that will be further optimized for biotechnological applications.